Opening the Door to Nature: Accounting for People’s Constraints to Nature-based Recreation - Margaret E. Gullion; Taylor Stein (EDIS)
Although millions of people recreate in parks, forests, and other conservation areas in the United States every year, research shows that some are left out; not everyone takes advantage of natural areas for the numerous benefits nature-based recreation provides. Results show that many people who do not participate in nature-based recreation feel constrained by their quality of time, not the quantity of time. In other words, they're saying, "Prove to me that it's worth my time to go out in nature. Show me something cool!" Based on research conducted in Hillsborough County, Florida and similar studies, this 6-page fact sheet written by Margaret E. Gullion and Taylor Stein and published by the UF/IFAS School of Forest Resources and Conservation addresses identifies strategies to improve the opportunities natural areas can provide a diverse public. https://edis.ifas.ufl.edu/fr415